Associations of monitor-assessed activity with performance-based physical function - Reid, N.; Daly, R.; Winkler, E.; Gardiner, P.; Eakin, E.; Owen, N.; Dunstan, D.; Healy, Genevieve (Public Library of Science, 2016)
The purpose of this study was to investigate the cross-sectional associations of monitorderived measures of sedentary time and physical activity with performance-based physical function in healthy Australian adults. Data from 602 participants (mean age 58.1 ±10.0 years; 58% female) from the 2011/12 wave of the Australian Diabetes, Obesity and Lifestyle (AusDiab3) study were analyzed. The thigh-worn activPAL3™ monitor (7-days continuous wear) was used to derive time during waking hours spent: sitting/reclining; standing; and, stepping (overall, and separately as light [<3 METs] and moderate-to-vigorous physical activity [MVPA; =3 METs]), and number of sit-stand transitions. Associations of these (in hours/day, or 15 transitions/day) with physical function measures (8ft Timed Up and Go [TUG-8; log-transformed seconds] and Knee Extensor Strength [KES; kg]) were tested via linear regression, adjusting for confounders. Interactions by sex and age-category (<45; 45-54; 55-64; =65 years) were tested. In all participants, KES was significantly (p<0.05) associated with stepping and MVPA stepping only; none of the activity measures were associated with TUG-8. However, subgroup analysis revealed that in older adults (=65 years), TUG-8 was associated with stepping and MVPA stepping (both p<0.05). All associations with sitting time, standing, sit-stand transition and sex interactions were not statistically significant. In summary, sitting time was not significantly associated with impaired muscle strength or gait/mobility in Australian adults aged 36-80 years, but light- to moderate activity (stepping) was positively associated with muscle strength, and gait/mobility in older adults aged =65 years. The direction of causation is not known and remains important to investigate considering the high prevalence of both poor function and limited activity in older age.